2015
DOI: 10.4236/ojpsych.2015.52016
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Prescribing Patterns for Depressive and Anxiety Disorders in a Singapore Hospital

Abstract: Objective: Although antidepressants are the recommended first-line pharmacological treatments for depressive and anxiety disorders, their prescribing patterns have not been studied in Singapore. We investigate antidepressant prescription patterns for outpatients with depressive and anxiety disorders in a general hospital in Singapore. We hypothesize that intolerance to side effects and lack of efficacy may contribute to medication switching, and that initiation of antidepressant therapy is not easily tolerated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 30 publications
(35 reference statements)
0
17
1
Order By: Relevance
“…This would enhance rational prescribing and affordability. In contrast to the findings of this study, SSRIs were the most frequently prescribed drugs in studies carried out in Asia, Europe, North America and India [3,14,15,21,[31][32][33][34] with decreased use of TCAs. Factors such as differences in culture, practice, promotional activity [32,35,36] and national income [37] contribute to these regional differences.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This would enhance rational prescribing and affordability. In contrast to the findings of this study, SSRIs were the most frequently prescribed drugs in studies carried out in Asia, Europe, North America and India [3,14,15,21,[31][32][33][34] with decreased use of TCAs. Factors such as differences in culture, practice, promotional activity [32,35,36] and national income [37] contribute to these regional differences.…”
Section: Discussioncontrasting
confidence: 99%
“…This is similar to the findings of other researchers. [3,21,22] This occurrence is hypothesized to be due to hormonal influence, the effect of child birth and different psychosocial stress among women. [23] Contrary to the view that SSRIs are preferred over older classes of antidepressants owing to less severe adverse effects, TCAs accounted for 61.3% of antidepressants used in the hospital under study; with SSRIs as only (38.7%).…”
Section: Discussionmentioning
confidence: 99%
“…We identi ed fteen studies through this review, and the majority of the patients were in the economically productive age group of 40-50 years [25][26][27][28][29][30][31][32][34][35][36][37][38][39] , whereas in the result of a study on antidepressant use in Italy, the mean age of the patients who received antidepressant prescriptions was more than 50 years 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Our review showed that the majority of the patients receiving antidepressants for the treatment of their depression were females 27,[30][31][32][33][34][35][36][37][38][39][40][41][42][43] . This could be due to hormones that are associated with the regulation of the menstruation cycle and pregnancy affecting mood in females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation